Epidermolysis bullosa: management complexities for paediatric patients - Lynne, Victoria; Burns, Lisa; Handsaker, Joanne; Murdoch, Julie M (British journal of nursing (Mark Allen Publishing), 2018)
The genetic skin condition, epidermolysis bullosa (EB) causes the skin to be fragile and blister. As a result, blisters need to be lanced and the skin needs to be dressed with specialist dressings for protection and to promote wound healing. a prospective case series and product evaluation of the Allevyn™ Gentle Border Lite dressing range was conducted, with four paediatric patients diagnosed with the following types of EB: recessive dystrophic (generalised severe), dominant dystrophic, simplex (generalised severe) and junctional (localised). Specialist EB nurses at Birmingham Children's Hospital conducted the evaluation and compiled the case series. Management and outcomes: clinical, patient and health economic outcomes were captured. The outcomes reported suggest an increase in dressing time wear and a reduction in dressing changes when comparing Allevyn Gentle Border Lite dressings to the patient's regular foam dressing regime. Furthermore, a cost saving measure could be shown. this small case series suggests that the use of the Allevyn Gentle Border Lite dressing range can positively impact the clinical, patient and health economic outcomes of paediatric EB patients.